Leukoaraiosis and increased cerebral susceptibility to ischemia: lack of confounding by carotid disease. - Schulz, U; Grüter, B; Briley, D; Rothwell, P (2013)
BACKGROUND: Leukoaraiosis is associated with an increased risk of stroke, but the underlying mechanism remains uncertain, as do the associations with other risk factors, such as carotid disease. We aimed to determine the role of carotid disease and of other clinical variables in the development of leukoaraiosis and to define their contributions to the associated increased risk of stroke. METHODS AND RESULTS: We prospectively studied a large cohort of consecutive patients with transient ischemic attack (TIA) and minor stroke who attended a TIA clinic between 2002 and 2009. Detailed clinical data were obtained, and patients underwent magnetic resonance brain and vascular imaging. We assessed the severity of leukoaraiosis with use of the ARWMC (Age Related White Matter Changes) score: 671 patients (374 [56%] men; mean [SD] age 71 [11] years) were studied, of whom 415 (62%) had leukoaraiosis. In a multivariate analysis, leukoaraiosis was associated with increasing age (P<0.0001) and hypertension (P=0.01), as well as the presence of acute (P<0.0001) and chronic (P=0.014) infarction on magnetic resonance imaging. In the univariate analysis, a current and past diagnosis of stroke versus TIA also showed a strong association. Carotid disease was not associated with leukoaraiosis, even in the presence of a flow-limiting (>70%) stenosis or occlusion, and the risk factor profiles for leukoaraiosis and carotid disease differed. CONCLUSIONS: The association with more severe ischemic events (stroke versus TIA) and infarction on imaging is consistent with leukoaraiosis being a marker of increased cerebral susceptibility to ischemia. In contrast, the presence, severity of, and risk factors for atheromatous disease showed no association with leukoaraiosis, suggesting that these are two unrelated disease processes.